PENGELOMPOKAN PENDISTRIBUSIAN PRODUK OLAHAN AYAM MENGGUNAKAN ALGORITMA K-MEANS - Heri Gunawani; Ria Eka Sari; Sari Rizky (STMIK KAPUTAMA, 2019)
Increasing population growth in Indonesia has triggered a large number of food product demand, so the higher the level of innovation of the company to produce processed food. PT Charoen Pokphand Indonesia Food Division is one of the companies engaged in processed food made from chicken meat. However, companies currently have not been able to process distribution data and rely solely on information from sales data to find out the number of product sales with which brands are sold the most each year. In fact, it is not enough to increase income and to be able to compete with other similar companies. From the existing data stack, it must be processed to find out new information from these data. Data processing methods like this are referred to as data mining. the results of cluster 3, again - it is seen that consumer characteristics in cluster 3 are also dominated by consumers who are more interested in Okey's processed chicken products, which is as much as 5615.67 Pack / Box. Whereas for enthusiasts in processed chicken products with the Fiesta brand as many as 4614.67 Pack / Box. and enthusiasts of processed chicken products under the Champ brand 1792.67 Pack / Box. So, from all clusters, it can be concluded that cluster 3 consists of cities with the lowest sales level.